Aerospace series. Screws, pan head, Spiral Drive Recess, threaded to head, in heat and corrosion resisting steel, passivated. Classification : 1 100 MPa (at ambient temperature) / 425 °C. (11th April 2022) - British Standards Institution,
No abstract available